Pengaruh Financial Distress dan Insentif Pajak Terhadap Konservatisme Akuntansi (Studi Pada Perusahaan Sektor Transportasi yang Terdaftar di BEI Periode 2017-2019) - Rasmon Rasmon; Safrizal Safrizal (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2022)
This study aims to examine and analyze the effect of financial distress and tax insentif on accounting conservatism. The population in this study are transportation sector companies listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling technique used purposive sampling method which resulted in 20 companies as samples. The data used is secondary data, where financial distress and tax insentif are independent variables, accounting conservatism is the dependent variable. The research analysis technique used is descriptive analysis and path analysis using SPSS software. The results of this study indicate that financial distress and tax insentif Â affect on accounting conservatism in transportation sector companies on the IDX.Â Keywords: Financial Distress, Tax Insentif, and Accounting Conservatism.